Comparison of two panels of monoclonal antibodies for determination of Chlamydia trachomatis serovars. - Ossewaarde, J M (1994)
A panel of monoclonal antibodies was developed for serovar typing of clinical isolates of Chlamydia trachomatis. The panel could distinguish all 15 established serovars from one another, although the hybridomas of the panel were developed by fusions of myeloma cells and spleen cells from mice immunized with antigen derived from the urogenital serovars D to L3. The typing assay was based on a dot enzyme immunoassay, and the monoclonal antibodies that were included in the panel reacted strongly in this assay. A collection of 289 clinical isolates from The Netherlands was typed. The observed serovar frequency distribution was 51 isolates of serovar D (17.6%), 103 isolates of serovar E (35.6%), 62 isolates of serovar F (21.5%), 28 isolates of serovar G (9.9%), 14 isolates of serovar H (4.8%), 2 isolates of serovar I' (0.7%), 20 isolates of serovar J (6.9%), and 9 isolates of serovar K (3.1%). These results were confirmed by typing these isolates with a panel of monoclonal antibodies purchased from the Washington Research Foundation, Seattle. No strain variation was observed within serovar D with both panels. However, restriction fragment length polymorphism analysis of the gene encoding the major outer membrane protein showed that 32 isolates were similar to the prototype D and 17 were similar to the variant D-. The two others showed a new restriction pattern. Our panel of monoclonal antibodies contained one monoclonal antibody that divided the serovar G isolates into two groups. This differentiation was confirmed by restriction fragment length polymorphism analysis, confining this difference to a known sequence variation in variable domain IV. These data support the subdivision of serovar G into serovars G (prototype strain UW-57) and Ga (prototype strain IOL-238).